Strategi Dakwah dalam Membina Kehidupan Beragama Masyarakat Perkotaan (Studi Kasus pada Masjid An-Nur Menara Mandiri Sudirman DKI Jakarta) - Chairul Umam; Abdul Hamid; Sarbini Anim (Jurnal Studi Pendidikan Agama Islam, 2026)
Massive urbanization in Indonesian metropolitan areas presents distinct challenges for cultivating religious life among professional communities. This study examines the da'wah strategy of Masjid An-Nur Menara Mandiri Sudirman Jakarta as a representative corporate mosque operating within a Central Business District (CBD) environment. Employing a qualitative approach through intensive case study methodology, data were gathered over six months via participant observation, in-depth interviews, and documentary analysis. Three principal findings emerged. First, program planning is conducted through a participatory need assessment mechanism, producing an integrated da'wah ecosystem. Second, program implementation contextually applies the Qur'anic principles of al-hikmah, al-mau'izhah al-hasanah, and al-mujadalah bil-ahsan, supplemented by methodological innovations encompassing professional da'wah, spiritual mentoring, and transformative community formation. Third, program effectiveness is sustained by institutional support, da'i quality, digital infrastructure, and community cohesion, yet constrained by temporal limitations, congregation heterogeneity, and digital content competition. This study contributes a corporate da'wah model that holistically integrates theological, sociological, and managerial dimensions, offering an evidence-based reference for mosque management in major Indonesian urban centers.